EFEKTIVITAS PELAKSANAN PASTORAL DASAR DALAM MEMBENTUK SPRITUALITAS MAHASISWA PRODI PELAYANAN PASTORAL DI ERA DIGITAL - Bergita Layon Herin; Lorentius Goa (Jurnal Pelayanan Pastoral, 2025)
This research aims to explore the effectiveness of basic pastoral implementation in shaping the spirituality of students of the Pastoral Service Study Program at the Indonesian Pastoral College of the IPI Malang Foundation, who live in the digital era. Basic pastoral is an important foundation in building the character and spiritual life of students as prospective pastoral ministers. This study uses a qualitative approach with a descriptive approach. The data collected in this study through in-depth interviews with ten students were selected based on their involvement in basic pastoral practice as well as their experience in carrying out basic pastoral practices. The research informants consisted of two first-year students, two second-year students, two third-year students, and three fourth-year students. The results of the study show that basic pastoral implementation is the foundation in the spiritual life of students in the digital era. have a significant impact on the formation of students' spirituality, strengthen their faith, and prepare them to face the challenges of the digital age with spiritual faith and maturity. Activities such as meditation, scripture reading, worship/eucharist, self-formation, and community interviews help students strengthen their relationship with God. Although the digital world is often challenging, the basic pastoral helps students to stay focused on their spiritual life, as well as form spiritual discipline, build awareness of God's presence, and teach them how to use their time wisely, so that they can maintain a balance between the digital world and spiritual life.